Multiple Extramedullary Plasmacytoma with Lytic Bony Lesions: A Rare Case Report - Akhlak Hussain; Mohinder Singh; Kuldip Singh; Harjot Bagga (Case Reports in Medicine)
Objective. Multiple extramedullary plasmacytoma lesions involving subcutaneous tissue, breast, mediastinal tissue, spleen, and soft tissue of pelvic region along with multiple bones plasmacytomas without marrow plasmacytosis are a very rare presentation. Design. Case report. Result. A 54-year-old female was found to have multiple small bony lytic lesions, multiple extramedullary soft tissue plasmacytomas, serum M protein >3 g/dL, and elevated ESR. Bone marrow aspirate did not reveal any evidence of multiple myeloma/plasmacytosis. There was no anemia, hypercalcemia, or renal insufficiency. Conclusion. Extramedullary plasmacytoma can involve multiple organs at a time including bones and soft tissue without involving bone marrow.